Madu Sebagai Obat Dalam Perspektif Al-Qur’an: An-Nahl 68-69 - Kaysa Billah; Nilla Sari; Ali Akbar (PT. Saha Kreasi Indonesia, 2025)
Honey is one of the natural substances that has been used as medicine for thousands of years. In the Qur'an, specifically in Surah An-Nahl verses 68-69, Allah explicitly mentions honey as containing shifa (healing) for humans. This article examines the concept of honey as medicine from a Qur'anic perspective by analyzing the interpretation of related verses, the scientific content of honey, and its relevance to modern health research. The method used is a literature review (library research) with a thematic (maudhu'i) interpretation approach. The research findings indicate that the Qur'an preceded modern scientific discoveries about the therapeutic properties of honey, and there is a strong correlation between the Qur'anic statements and contemporary scientific evidence regarding the benefits of honey as a healing agent.